Rethinking New Womanhood Practices of Gender, Class, Culture and Religion in South Asia (Springer International Publishing, 2018)
Covering India, Bangladesh, Pakistan and Nepal, Rethinking New Womanhood effectively introduces a 'new' wave of gender research from South Asia that resonates with feminist debates around the world. The volume conceptualises 'new womanhood' as a complex, heterogeneous and intersectional identity. By deconstructing classification systems and highlighting women's everyday ongoing negotiations with boundaries of social categories, the book reconfigures the concept of 'new woman' as a symbolic identity denoting 'modern' femininity at the intersection of gender, class, culture, sexuality and religion in South Asia. The collection maps new sites and expressions on women and gender studies around nationhood, women's rights, transnational feminist solidarity, 'new girlhoods ', aesthetic and sexualised labour, respectability and 'modernity', LGBT discourses, domestic violence and 'new' feminisms. The volume will be of interest to students and scholars across a range of disciplines including gender studies, sociology, education, media and cultural studies, literature, anthropology, history, development studies, postcolonial studies and South Asian studies.